The End of Bias: A Beginning: The Science and Practice of Overcoming Unconscious Bias - Keaton West Hernandez Hernandez (Journal of College Orientation, Transition, and Retention)
The End of Bias by Jessica Nordell is a compelling examination of racism and sexism, including with relatable analogies and real-life examples to better explain scientific concepts. Nordell offers strategies grounded in research that have successfully mitigated bias and proposes methods to apply these strategies in various settings. The book is structured into three parts: How Bias Works, Changing Minds, and Making It Last. Part 1 explores the historical and psychological foundations of bias, emphasizing its cumulative nature. Part 2 presents successful interventions in police departments, communities, and schools, highlighting programs like The Madison Workshop and initiatives to reduce police stress and improve community relations. Part 3 discusses systemic changes required to sustain bias reduction, with chapters addressing healthcare inequities, the impact of diversity in professional settings, and the necessity of structural and cultural shifts within organizations. While the book effectively opens dialogue on bias and suggests practical measures for its reduction, it acknowledges that ending bias entirely requires widespread and profound societal changes. Nordell's work is a valuable resource for higher education and professional development, offering a starting point for discussions and actions aimed at reducing bias.